(3GdeMjW GdeLehY aj GdCUhd hGdaQhY aj GdfMhs - (3SGHb GdOjf eMeO Hf Ydj Hf CMeO GdUZGfjs
(3ChdgG (B:s
(3HGH GdfOGA s
(3BNQgG (B:s
(3jfJgi HaUd ai CMcGe eP hefP , hBNQ eG ajg (B: (3hef LedI CMcGe eP hefP CfgeG dGjONdGf Ydi eVeQ HGdEJbGa , hbO JbOe s
(3GdLRA GdKGfi ef KdGKI CLRGAs
(3HChdgG bQGAI dYOI cJH SfI (B551 (3g` hbO JZjQ Gdbde ai gPg GdfSNI YOI eQGJs
(3HChdgG Jedc HGSe eMeO Hf jMji GdfMhis
(3hjMi Hf eMeO GdfMhi s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdfMhs